Hydraulic Control of Air Pressure in Solution Blown Spinning Technology for Producing Recycled Nano-fibers - Hossen, Shadi; Tuhmaz, Ghazal; Alshaar, Kinan (Nanoscience & Nanotechnology-Asia, 2025)
IntroductionThe nonwoven fabric industry has witnessed significant developments in recent years, with the emergence of diverse production methods to meet various needs and applications. Recently, a new technology has been developed for the production of nonwoven fabrics made from micro and nanofibers, known as solution blown spinning. This technology boasts high productivity and enables the manufacture of industrially viable webs. The air compressor in solution blown spinning machines is the most important component, as it pumps high-pressure air to blow the polymer material and form the fibers. Therefore, the air pressure used is a critical factor, as it ensures the high velocity of the compressed gas, which generates the shear force necessary for blowing the polymer and forming the fibers. Thus, the objective of this study was to investigate the effect of varying the high air pressure exiting the compressor cylinder on the properties of the resulting fiber web, including its composition, diameter, density, and productivity.MethodsAir pressure values were changed using a pressure gauge installed on the compressor outlet nozzle within a range of 1-5 bar. A blow-spinning process was carried out to form five nanofiber webs using a 7% weight-percent poly (lactic acid) solution at each pressure value, while keeping the other process parameters constant. The resulting webs were examined microscopically using SEM. The resulting microscopic images were then processed using Image J software, and the average fiber diameters, densities, and productivity were calculated for each sample based on the solution flow time. The results were then discussed graphically and statistically.ResultsThe results indicated that the fiber formation process was better at lower pressures, with higher densities and smaller diameters on the nanoscale. The average fiber diameters within the studied pressure ranged between 554.7 and 1342.1 nm, and the smallest diameter measured was 350 nm. The statistical study also demonstrated a difference between fiber diameters. Essentially, the study yielded impressive results for fiber specification values. The fiber density in the surface layer of the samples also decreased with increasing air pressure, which is consistent with the results showing an increase in diameter. This led to a decrease in the polymer solution consumption time, accompanied by an increase in the solution flow rate, which doubled the production of fiber networks on the blower.DiscussionThe study demonstrated the possibility of controlling the diameters of the nanofibers to be produced before initiating the production process by calibrating the air pressure value exiting the cylinder and thus evaluating their speed during operation. In addition, the importance of using polylactic acid waste resulting from 3D printing, recycling it, and converting it into biodegradable and environmentally friendly nonwoven nanofibers was highlighted. These products could find wide future applications in medicine, healthcare, and environment fields by being used as nano-filters.ConclusionThe results of this research can be used as a basis for research conducted within the context of developing blow-spinning technology. We also propose the use of cameras to monitor the airflow during the rotary blowing process, measure air speed, determine product specifications, and compare them with the results of the hydraulic study presented in this research. If the results are consistent, the cost of equipment used in future research can be reduced by relying on the computational fluid dynamics calculations presented in this manuscript.
Keywords: hydraulic control